A patch antenna array for IFF band - Mička, J.; Láčík, J.; Martinec, M. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
This paper describes a design of an antenna array for the IFF band. The array consists of four antenna elements arranged as a 2 × 2 matrix. A single antenna is designed as two stacked patches, fed by a slot. The feeding network is designed as an asymmetric stripline. Simulations of the proposed antenna array give good simulation results especially VSWR lower than 1.5.
Keywords: antenna array; stacked patches; aperture-coupled; stripline